Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/hed.20525
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cell cycle arrest and apoptosis by a combined treatment with 13‐cis‐retinoic acid, interferon‐α2a, and α‐tocopherol in squamous cell carcinoma of the head and neck

Abstract: Our data suggests that 3-drug combination biochemopreventive regimen has cooperative inhibitory effect on the growth of SCCHN cells. Both cell cycle arrest and apoptosis contribute to cell growth inhibition of this 3-drug combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
(50 reference statements)
2
6
0
Order By: Relevance
“…22 Also, AT as a single agent or combination with other chemopreventive agents inhibited cellular proliferation and induced apoptosis in cell lines of gastrointestinal tract cancer. 15,23 Our results confirmed the growth inhibitory effect of AX and AT in TE-4 esophageal cancer cell line. However, the fixed concentration of AT (100μM) which inhibited cellular proliferation was higher than that of other study (15μM) which showed such effect in squamous head and neck cancer cell line.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…22 Also, AT as a single agent or combination with other chemopreventive agents inhibited cellular proliferation and induced apoptosis in cell lines of gastrointestinal tract cancer. 15,23 Our results confirmed the growth inhibitory effect of AX and AT in TE-4 esophageal cancer cell line. However, the fixed concentration of AT (100μM) which inhibited cellular proliferation was higher than that of other study (15μM) which showed such effect in squamous head and neck cancer cell line.…”
Section: Discussionsupporting
confidence: 79%
“…However, the fixed concentration of AT (100μM) which inhibited cellular proliferation was higher than that of other study (15μM) which showed such effect in squamous head and neck cancer cell line. 15 Our findings also suggested that AX and AT as single progression at the G0/G1 phase. 24 Our study showed that AX and AT as a single agents increased the expression of p27, however could not demonstrate accompanying decreased activity of cyclin D1.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Three-drug combination induced significant accumulation of the cells at S-phase and induced apoptosis. These data supported the promising outcomes of the phase III trial with a combination of these three drugs in patients with advanced head and neck cancer in the adjuvant settings [62].…”
Section: Head and Neck Squamous Cell Carcinoma (Hnscc) (Table 2)mentioning
confidence: 56%
“…They inhibit the cell proliferation of normal and malignant cells, modulate cell differentiation and trigger apoptosis (14)(15)(16)(17)29,(32)(33)(34). The cells are triggered in a G0/G1 cell cycle arrest thus prolonging the effectivity of the retinoids.…”
Section: Introductionmentioning
confidence: 99%